2012
DOI: 10.1152/ajprenal.00640.2011
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring urea transport in rat kidney in vivo using hyperpolarized13C magnetic resonance imaging

Abstract: DB. Monitoring urea transport in rat kidney in vivo using hyperpolarized 13 C magnetic resonance imaging. Am J Physiol Renal Physiol 302: F1658 -F1662, 2012. First published April 4, 2012 doi:10.1152/ajprenal.00640.2011.-Urea functions as a key osmolyte in the urinary concentrating mechanism of the inner medulla. The urea transporter UT-A1 is upregulated by antidiuretic hormone, facilitating faster equilibration of urea between the lumen and interstitium of the inner medullary collecting duct, resulting in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 19 publications
2
66
0
Order By: Relevance
“…This is supported by our recent study showing maintained sodium and urea gradients in the early diabetic kidney (two weeks after induction of diabetes) (18), while the intrarenal urea T2 relaxation time was reduced significantly already at 2 weeks due to increased oxygen consumption (23). The oxygen sensitivity of hyperpolarized urea has been shown to be a particular sensitive surrogate marker of metabolic status showing the altered demand during antidiuresis and diuresis in addition to the altered distribution (8,18,24). Albeit a similar intrarenal relaxation gradient is seen in both healthy and diabetic kidneys (23,24), it is unlikely that these relaxation effects dominates the distribution pattern seen here, but they are believed to contribute to the apparent intrarenal signal gradient as the balanced steady state sequence is sensitive to both T1 and T2 relaxation.…”
Section: Discussionmentioning
confidence: 59%
“…This is supported by our recent study showing maintained sodium and urea gradients in the early diabetic kidney (two weeks after induction of diabetes) (18), while the intrarenal urea T2 relaxation time was reduced significantly already at 2 weeks due to increased oxygen consumption (23). The oxygen sensitivity of hyperpolarized urea has been shown to be a particular sensitive surrogate marker of metabolic status showing the altered demand during antidiuresis and diuresis in addition to the altered distribution (8,18,24). Albeit a similar intrarenal relaxation gradient is seen in both healthy and diabetic kidneys (23,24), it is unlikely that these relaxation effects dominates the distribution pattern seen here, but they are believed to contribute to the apparent intrarenal signal gradient as the balanced steady state sequence is sensitive to both T1 and T2 relaxation.…”
Section: Discussionmentioning
confidence: 59%
“…64 Recent work has shown that it can also be used to measure absorption in diuresis and assess kidney function. 65 While many clinical studies employ CT and MR contrast agents, these tend to use high concentrations of iodinated contrast or Gd-chelates, which are not safe for patients with renal disease. 66,67 Thus perfusion imaging using HP 13 C urea has high potential for clinical translation.…”
Section: Considerations For Dnp Probe Developmentmentioning
confidence: 99%
“…Another in vivo rat study demonstrated that the T 2 of [ 13 C, 15 N]urea in kidneys was greater than ten seconds, as opposed to 1.3 seconds in blood, likely due to deoxyhemoglobin-induced paramagnetic relaxation in blood [119]. Finally, an in vivo rat study demonstrated more rapid medullary [ 13 C]urea enhancement in the antidiuretic state, suggesting that [ 13 C]urea could be used as a marker for urea transporter UT-A1 activity [261]. …”
Section: Hyperpolarized Studies By Organ Systemmentioning
confidence: 99%